Crafting Cities for All: Qualitative Inquiry of the Street and the Spatial Practice of Skateboarding. (August 2021) - Vivoni, Francisco; Folsom-Fraster, Jacob
This article exposes skateboarding as a meaningful social practice within neoliberal public space. Through a qualitative inquiry of the street, it chronicles the significance of moving bodies on skateboards that disrupt neoliberalism and foment the possibility of inclusive cities. The article takes on an invitation for researchers to practice qualitative inquiry in the streets as part of its living ecology through the corporeal knowledge produced while skateboarding in Worcester, MA, USA. Furthermore, it builds on an embodied inquiry of street art and spatial justice set on challenging deep social inequalities exacerbated during the current neoliberal order. The article forwards a street inquiry of everyday life centered on skateboarding, public space and the crafting of cities for all.